PERAN KEPEMIMPINAN SPIRITUAL TGKH. MUHAMMAD ZAINUDDIN ABDUL MADJID DALAM IMPLEMENTASI KURIKULUM MA’HAD DARUL QUR'AN WAL HADITS NAHDLATUL WATHAN - Samsul Hadi (STAI Ma'had Aly Al-Hikam Malang, 2026)
Abstract. This study aims to analyze the role of TGKH. Zainuddin Abdul Madjid’s spiritual leadership in the implementation of the curriculum at Ma’had Darul Qur’an Wal Hadits Nahdlatul Wathan. The research employed a qualitative case study approach. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, display, and verification techniques. The findings reveal that spiritual leadership functions as both an ideological and operational foundation in educational management. The values of tawhid, sincerity, role modeling, and educational struggle are integrated into the curriculum structure and academic culture of the pesantren. Implementation is carried out through role modeling, habituation of collective worship, and academic-spiritual integration. The impact is reflected in students’ intellectual competence, consistency in worship, and strong moral character. This study confirms that successful curriculum implementation in Islamic boarding schools is strongly influenced by spiritual leadership capable of transforming values into a sustainable educational system.